Transit of Sun Across Constellation Sagittarius and Variation of Secondary Gamma Radiation Flux in January, 2021 at Udaipur, India - Purohit, Prajesh; Pareek, Devendra (Nepal Journal of Science and Technology, 2021)
We experimentally observed the variation of secondary gamma radiation flux (SGR) at Udaipur (27° 43’ 12.00” N, 75° 28’ 48.01” E), Rajasthan, India during transit of Sun across constellation Sagittarius in month of January, 2021. In this experimental study we used ground based NaI (Tl) Scintillation detector. Cadences of data were collected at interval of half an hour. The data files were stored in computer for half hour duration around time 17.00 IST to 17.30 IST on January 8, 9, 11, 13, 14, 17 and 18. The objective in this study is to observe secondary gamma radiation flux during transit of the Sun across the constellation Sagittarius. Analyzed data reveal significant variation of secondary gamma radiation flux (SGR). We interpret such variation of SGR flux counts on the basis of combine gravitational lensing effect due to Sun and Sagittarius constellation on background radiation, gravitational pull effect by constellation and sun on background radiation and radiation from constellation Sagittarius.